Pelatihan Karawitan Di Grup Karawitan Mojolaras Kelurahan Mojosongo Dan Grup Karawitan Maju Mawas Benowo Ngringo Jaten Karanganyar: Salah Satu Usaha Demi Ketahanan Kehidupan Seni Karawitan Di Era Globalisasi - Supardi Supardi (Institut Seni Indonesia Surakarta, 2016)
The ability to master musical compositions for the gamelan is an essential professional skill that members of the Mojolaras and Majumawas Karawitan groups must possess. Gamelan groups whose members are artists with minimum experience and a lack of musical education require intensive rehearsals in order to master these musical compositions. These rehearsals are intended to help the Mojolaras Karawitan Group in Mojosongo, Jebres, Surakarta, and theMajumawasKarawitanGroupÂ in Benowo, Ngringo, Jaten, Karanganyar to become familiar with a wide repertoire of compositions and the different ways of treating these compositions. The members of these groups are aware of the need to rehearse, bearing in mind that they often have the opportunity to perform at weddings, circumcisions, and other community events.Keywords :Gamelan,MajumawasKarawitan